2017
DOI: 10.1016/j.jaci.2016.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary sarcoidosis is associated with exosomal vitamin D–binding protein and inflammatory molecules

Abstract: Together, these data contribute to understanding the role of exosomes in lung disease and provide suggestions for highly warranted sarcoidosis biomarkers. Furthermore, the validation of an exosome-associated biomarker in the blood of patients provides novel, and less invasive, opportunities for disease diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 40 publications
0
37
0
3
Order By: Relevance
“…Показа-но, что кальцитриол снижает продукцию Тх-цитокинов и увеличивает продукцию су-прессорных цитокинов TGF-β1 и IL-4. При туберкулезе активация микобактериальны-ми антигенами ТОЛЛ-рецепторов приводит к повышению экспрессии витамин Д рецеп-торов и 1α-дегидрогеназ, которые индуци-руют продукцию кателицидина и киллинг M. Tuberculosis [3].…”
Section: Abstract: Tuberculosis Children Adolescents Vitamin D Binunclassified
See 2 more Smart Citations
“…Показа-но, что кальцитриол снижает продукцию Тх-цитокинов и увеличивает продукцию су-прессорных цитокинов TGF-β1 и IL-4. При туберкулезе активация микобактериальны-ми антигенами ТОЛЛ-рецепторов приводит к повышению экспрессии витамин Д рецеп-торов и 1α-дегидрогеназ, которые индуци-руют продукцию кателицидина и киллинг M. Tuberculosis [3].…”
Section: Abstract: Tuberculosis Children Adolescents Vitamin D Binunclassified
“…ВДБ связанный с экзосома-ми определялся у больных в достоверно более высокой концентрации. Помимо это-го фактора в более высоких концентрациях с экзосомами были связаны различные гли-копротеины, липополисахарид-связываю-щий белок, кининоген-1, лактотрансерин, протромбин, серотрансферрин, гаптогло-бин, аполипопротеин, белки мембрано-ата-кующего комплекса (МАС) и ферменты ме-таболизма лейкотриена 4 [3].…”
Section: Abstract: Tuberculosis Children Adolescents Vitamin D Binunclassified
See 1 more Smart Citation
“…Susanne Gabrielsson (Stockholm, Sweden) presented exosomes as potential biomarkers in human lung diseases. She demonstrated that bronchoalveolar lavage fluid (BALF)-derived exosomes from sarcoidosis patients carry higher levels of vitamin-D binding protein compared with controls [5]. Exosomes from sarcoidosis patients have leukotriene-dependent pro-inflammatory properties and trigger interleukin-1β production in macrophages.…”
Section: Assembly 3: Basic and Translational Sciences (Olivier Burgy)mentioning
confidence: 99%
“…In sarcoidosis, serum miRNA have been reported to differ between patients with Löfgren's syndrome (LS), an acute form of sarcoidosis with well‐defined clinical features and non‐LS . BAL exosomes from sarcoidosis patients have been shown to induce higher amounts of interferon gamma (IFNγ) and interleukin (IL)‐13 from autologous peripheral blood mononuclear cells and to contain increased amounts of vitamin‐D‐binding proteins compared with healthy controls. However, these studies have not investigated population subtypes of EV, which has been strongly recommended due to their different origins, sizes, characteristic protein markers and their role in the delivery of biomolecules during cellular communication .…”
Section: Introductionmentioning
confidence: 99%